2020
DOI: 10.1155/2020/3501749
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Ejection Fraction Is Associated with the Risk of Thrombus in the Left Atrial Appendage in Patients with Atrial Fibrillation

Abstract: Introduction. Atrial fibrillation (AF) is associated with high risk of ischemic stroke. The most frequent thrombus location in AF is the left atrial appendage (LAA). Transthoracic echocardiography (TTE) is a basic diagnostic examination in patients (pts) with AF. Objectives. To analyse the relations between basic echocardiographic features, well-established stroke risk factors, type of AF, and anticoagulation therapy with the incidence of left atrial appendage thrombus (LAAT). Patients and Methods. The study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
3
16
0
2
Order By: Relevance
“…As shown in Table 1, patients who developed AF were older, had a high body mass index (BMI) tendency, and the AF patients usually had greater left ventricular end-systolic diameter (LVDd), left ventricular end-systolic diameter (LVDs), and left atrium (P<0.05). Consistent with previous reports (12), left ventricular ejection fraction (LVEF) was decreased in AF patients (Table 1). Concerning the concentrations of the biomarkers at baseline, the AF patients had higher levels of neutrophil (NE), creatine kinase MB (CK-MB), urea nitrogen (BUN), creatinine, uric acid, potassium, total bilirubin (TB), direct bilirubin (DB), fibrinogen (Fbg), glycosylated hemoglobin (HbA1c), total triiodothyronine (TT3), and BNP (P<0.05) (Table 1).…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…As shown in Table 1, patients who developed AF were older, had a high body mass index (BMI) tendency, and the AF patients usually had greater left ventricular end-systolic diameter (LVDd), left ventricular end-systolic diameter (LVDs), and left atrium (P<0.05). Consistent with previous reports (12), left ventricular ejection fraction (LVEF) was decreased in AF patients (Table 1). Concerning the concentrations of the biomarkers at baseline, the AF patients had higher levels of neutrophil (NE), creatine kinase MB (CK-MB), urea nitrogen (BUN), creatinine, uric acid, potassium, total bilirubin (TB), direct bilirubin (DB), fibrinogen (Fbg), glycosylated hemoglobin (HbA1c), total triiodothyronine (TT3), and BNP (P<0.05) (Table 1).…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…In this study, low LVEF was a predictor of high LA D-dimer levels. A previous study reported that decreased LVEF led to LA thrombus formation [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…In our analysis, decreased LVEF was revealed to be a powerful and independent predictor of LAT/LA-SEC formation in AF patients, which means high cardiogenic stroke risk. Previous studies have suggested that incidence of LAT depending on LVEF, and severe LV systolic dysfunction (confirmed by echocardiography) was a strong predictor of stroke (32,33).…”
Section: Main Findingsmentioning
confidence: 96%